INCIDENTAL FINDINGOF LOW-GRADE APPENDICULAR MUCINOUS NEOPLASM IN PERFORATED APPENDICITIS: A CASE REPORT - Andrej Nikolovski; Nimetula Limani; Labinot Bekteshi; Gordana Petrushevska (KNOWLEDGE - International Journal, 2021)
We are presenting a case of a 36 years old male patient with clinical signs for acute appendicitis. Contrast-enhanced abdominal CT finding revealed a small periappendicular abscess and the patient was subjected for laparoscopic appendectomy for complicated appendicitis. Histologic analysis of the specimen revealed a Low-grade Appendicular Mucinous Neoplasm (LAMN) with dimension of 1 cm at the appendicular tip with histologic presentation of mucin-producing cells
Keywords: LAMN; perforated appendicitis